PERSEPSI TOKOH ULAMA TERHADAP TRADISI MANDI TIGA MALAM (Studi Adat Perkawinan Kerabat Keraton Kerajaan Matan, Kabupaten Ketapang, Kalimantan Barat) - Uti Maulana Yahya (Islamic Family Law, STAI Sangatta Kutai Timur, 2026)
This study examines the perceptions of Islamic scholars regarding the practice of the Mandi Tiga Malam tradition in a traditional wedding ceremony among members of the Matan Tanjungpura Palace family in Ketapang Regency, West Kalimantan. This field research employed an empirical legal approach. Data were collected through interviews and documentation involving local Islamic scholars and were analyzed using descriptive qualitative methods. The findings reveal two perspectives among the scholars. One supports the continuation and preservation of the tradition because of its educational values, local wisdom, and Islamic elements, such as the recitation of Shalawat and Prayers. The other accepts the tradition under certain conditions, emphasizing that it must be carried out selectively, free from elements of Shirk or Mysticism, and in accordance with Islamic law, including the obligation to maintain proper modesty during the bathing ritual.